Heparin in sepsis: current clinical findings and possible mechanisms - Yu, Sihan; Chi, Yawen; Ma, Xiaochun; Li, Xu (Frontiers in Immunology, 2024)
Sepsis is a clinical syndrome resulting from the interaction between coagulation, inflammation, immunity and other systems. Coagulation activation is an initial factor for sepsis to develop into multiple organ dysfunction. Therefore, anticoagulant therapy may be beneficial for sepsis patients. Heparin possesses a variety of biological activities, so it has a broad prospect in sepsis. Previous studies suggested that patients with sepsis-induced disseminated intravascular coagulation and high disease severity might be suitable for anticoagulant therapy. With the development of artificial intelligence (AI), recent studies have shown that patients with severe coagulation activation represent the targeted patients for anticoagulant therapy in sepsis. However, it remains necessary to accurately define the relevant biomarkers indicative of this phenotype and validate their clinical utility by large randomized controlled trials (RCTs). Analyses of data from early small RCTs, subgroup analyses of large RCTs and meta-analyses have collectively suggested that anticoagulant therapy, particularly the use of heparin, may be an effective approach for managing sepsis patients. Concurrently, debate persists regarding the optimal selection of anticoagulants, proper timing, usage and dosage of administration that should be employed to assess treatment efficacy. The primary mechanisms of heparin are acting on heparan sulfate, histones, high mobility group box 1 and heparin-binding protein, which interfere with the regulation of inflammation, vascular permeability, coagulation, endothelial function and other biological activities. However, the underlying pathophysiological processes mediating the potential therapeutic effects of heparin in the context of sepsis remain incompletely understood and warrant additional rigorous investigation to establish the mechanism more conclusively.